PERLINDUNGAN HUKUM TERHADAP KESELAMATAN DAN KESEHATAN KERJA KARYAWAN PT. PLN UPT SEMARANG - Widiatmoko, Hengky; Suparnyo, Suparnyo (Kertha Semaya : Journal Ilmu Hukum, 2024)
ABSTRACT   This study is to examine the legal protection of occupational safety and health of employees of PT PLN UPT Semarang about the rights of workers, namely the right to obtain protection against safety ". The formulation of the problem studied is how the legal protection of the safety and health of employees of PT PLN UPT Semarang employees and the obstacles and efforts made in providing employees of PT PLN UPT Semarang. The method in this research is non-doctinal research In this study, researchers used non-doctrinal legal research methods. This research is a type of legal examination that opens and sees how a rule applies in the eyes of the community, the population is PT PLN UPT Semarang and the research subjects are employees who work at the company. The method of data collection is done by means of direct research in the form of observation and interviews, besides that a literature study is used. In the data analysis method used is qualitative data analysis. Legal protection of the safety and health of employees of PT PLN UPT Semarang has been running well which is indicated by making efforts, namely the provision of personal protective equipment in the form of personal protective equipment, health and employment insurance facilities as well as counseling, coaching, and supervision of workers regarding their work. Keywords:  safety and occupational health, legal protection